The Influence of Human Capital on Employee Welfare: The Business of Jasmine Essential Oil as a Perfume Seed Product - Lindawaty, Lindawaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Jasmine essential oil is a crucial component in the perfume and cosmetics industry. Derived from jasmine flowers, it possesses a distinct and captivating aroma. The demand for jasmine essential oil has been escalating due to the continuous growth of the perfume industry. PT. Agrindo Sumber Harum is a company in this sector that specializes in producing fragrance seedlings from jasmine essential oil. The company is responsible for producing, packaging, and distributing high-quality fragrance seedlings. This quantitative research aims to explore the relationship between Human Capital and Employee Well-being within the context of PT. Agrindo Sumber Harum. The research methodology involves secondary data analysis, which utilizes existing data to test hypotheses or answer research questions. Secondary data, such as sales data, financial data, or company performance data, can be analyzed to assess the impact of employee segmentation on sales growth and return on investment (ROI). The research employs Partial Least Square (PLS) as the data analysis technique. The findings reveal a significant favorable influence of Human Capital on Employee Well-being. The study concludes that PT. Agrindo Sumber Harum’s implementation of Human Capital practices contributes to the well-being of employees and reinforces the connection between Human Capital and Employee Well-being.